The role of a bioresource research impact factor as an incentive to share human bioresources - Cambon-Thomsen, Anne; Thorisson, Gudmundur A; Mabile, Laurence (Nature genetics, 2011)
Bioresources need to be easily accessible to facilitate advancement of research. Besides technical and ethical aspects, a major obstacle for sharing them is the absence of recognition of the effort behind establishing and maintaining such resources.